Peranan Guru Pendidikan Agama Islam Dalam Meningkatkan Disiplin Ibadah Siswa Di MTS Muhammadiyah Pokobulo Kabupaten Jeneponto - Riyan Maualana; Wahdaniya; Abd. Azis Ridha (Advances In Education Journal, 2025)
This study aims to: (1) analyze the role of Islamic Education (PAI) teachers in enhancing students’ worship discipline, and (2) identify supporting and inhibiting factors. Using a qualitative descriptive method with observation, interviews, and documentation, data were collected from PAI teachers and students at MTs Muhammadiyah Pokobulo.Findings show that PAI teachers play a vital role not only in teaching but also as mentors and role models. Their roles include: guiding worship practices (Qur’anic studies, congregational prayers), educating with persuasive and empathetic methods, and modeling discipline through active worship and student leadership training (imam, muadzin). Worship discipline grows through consistent routines and a supportive school environment. Supporting factors include teacher involvement, collaboration, humanistic approaches, and structured programs, while inhibiting factors include students’ low awareness, environmental influences, and adolescent emotional instability. Continuous guidance nonetheless enhances students’ spiritual awareness and worship discipline.